Professional clubs as platforms in multi-sided markets in times of COVID-19: The role of spectators and atmosphere in live football - Herold, E.; Boronczyk, F.; Breuer, C. (Sustainability, 2021)
In-stadium spectators affect the emotional value and atmosphere of sport live broadcasts. Due to the COVID-19 pandemic, in Europe, the presence of in-stadium spectators, however, was suspended until further notice. Conceptualizing professional clubs as economic platforms, network effects due to the lack of in-stadium spectators may affect stakeholders` utility. Thus, the main aims of this study are to examine the influence of missing in-stadium spectators for professional clubs by investigating network effects on (1) TV viewers` emotional arousal and (2) TV viewers` attention towards sponsor messages during live football broadcasts. Using a quantitative research design, a controlled lap was conducted, and broadcasts were presented to n = 26 highly involved participants. Heart rate, eye-tracking, and betting odds data served as measurements of arousal, attention, and game outcome uncertainty and were aggregated on a second-by-second basis (k = 140,400). Multilevel regression analysis showed significant differences in viewers` arousal and attention to sponsors, contingent on the presence of in-stadium spectators and game outcome uncertainty. The presence of in-stadium spectators increased arousal, while attention towards sponsor messages decreased, depending on game outcome uncertainty. Based on the presence of network effects, implications to sustainably adapting professional football clubs` business models based on stakeholders` different interests can be given.